Growth of tiger grouper (Epinephelus fuscoguttatus) juvenile from wild and hatchery at different type of feeds - A. A. Muhammadar; A. G. Mazlan; Abdulah Samat; M. S. Asmawati (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
This study aimed to observe the influence of two sources of juvenile tiger grouper Epinephelus fuscoguttatus (Forsskål, 1775) from the sea and the hatchery by several types of food (pellets, tilapia anchovies). Growing Studies were carried out above 9600 juvenile tiger grouper from two sources namely differing from the sea of 4800 juvenile and 4800 juvenile hatchery from hatching. The design of treament were done by 2x3  with four replications. During the 30 day rearing period, each 5 days is taken  sampling total body length (cm) juvenile tiger grouper. The results showed that during the rearing period the value of marine juvenile grouper only high growth in juvenile ate anchovies and tilapia except on day 5 and 30, and could not adapt to the food from the pellet. While in hatchery juvenile tiger grouper had high growth to consume pellets only and could not adapt well to the food of tilapia and except anchovies on day 15th.